Cash transfers, gender norms, and women’s control over decision-making in Egypt - El-Enbaby, Hoda; Gilligan, Daniel O.; Karachiwalla, Naureen; Kassim, Yumna; Kurdi, Sikandra (University of Chicago Press, 2025)
Bargaining models predict that cash transfers targeted at women can increase women’s influence in household decisions; however, empirical evidence is mixed. We employ a fuzzy regression discontinuity design to identify the causal effect of Egypt’s national cash transfer program on women’s control over household decision-making. For women without education only, the transfers have large and significant negative effects on women’s ability to influence household decisions. The program also causes a decrease in women’s labor supply and an increase in husbands’ involvement in household decisions for women who have no education, suggesting two plausible pathways for the negative effect on women’s control over household decision-making. We also find that the program has no effect on several measures of gender norms, highlighting that these norms are entrenched rather than affected by the program. Additional results reveal that the negative effects on decision-making are concentrated among women who hold more restrictive gender norms and highlight the importance of norms for understanding the effects of cash transfers on intrahousehold dynamics.